Interaction of smoking, uptake of polycyclic aromatic hydrocarbons, and cytochrome P450IA2 activity among foundry workers. Issue 3 (March 1992) - Sherson, D; Sigsgaard, T; Overgaard, E; Loft, S; Poulsen, H E; Jongeneelen, F J
Abstract : An increased lung cancer risk has been described among foundry workers. Polycyclic aromatic hydrocarbons (PAHs) and silica are possible aetiological factors. This study describes a urinary PAH metabolite, 1-hydroxypyrene (hpU), as well as the degree of cytochrome P450IA2 activity/induction as reflected by the urinary caffeine ratio (IA2) in 45 foundry workers and 52 controls; IA2 was defined as the ratio of paraxanthine 7-demethylation products to a paraxanthine 8-hydroxylation product (1, 7-dimethyluric acid). Mean exposure concentrations for foundry workers were defined by breathing zone hygienic samples (respirable dust 1.2 to 3.52 mg/m3 (93 samples)) and as total PAH (0.46 micrograms/m3) and pyrene concentrations (0.28 micrograms/m3) (six samples). Non-smoking controls and foundry workers had similar IA2 ratios (5.63, 95% confidence interval (95% CI) 4.56-6.70 and 4.40, 95% CI 3.56-5.24). The same was true for smoking controls and foundry workers (9.10, 95% CI 8.00-10.20 and 8.69, 95% CI 7.37-10.01). Both smoking groups had raised IA2 ratios compared with non-smokers (p less than 0.01). Non-smoking controls and foundry workers had similar hpU concentrations (0.16, 95% CI 0.10-0.22 and 0.11, 95% CI 0.09-0.13 mumol/mol creatinine). Smoking foundry workers had raised hpU concentrations (0.42, 95% CI 0.25-0.59) compared with smoking controls (0.26, 95% CI 0.18-0.34) (p less than 0.01). A small subgroup of smoking foundry workers with the highest exposures to both silica and PAH also had the highest hpU concentrations (0.70, 95% CI - 0.07-1.47 mumol/mol creatinine) (p less than 0.04). Increased hpU concentrations in smoking foundry workers suggest a more than additive effect from smoking and foundry exposures resulting in increased PAH uptake. Increased P450IA2 enzyme activity was only found in smokers and no additional effect of foundry exposures was seen. These data suggest that smoking as well as work related PAH exposure may be casually related to increased risk of lung cancer in foundry workers.